OUTCOMES OF EMERGENCY LAPAROTOMY IN RESOURCE-LIMITED SETTINGS AT TERTIARY CARE HOSPITAL (The Research of Medical Science Review, 2025)
Emergency laparotomy (EL) is major surgery and a high-risk procedure, especially in resource-limited tertiary care hospitals; where patient characteristics and systemic challenges play a significant role in determining the outcome. This prospective observational study, carried out at a tertiary care hospital, Jinnah Postgraduate Medical Centre (JPMC), Karachi, aimed to determine clinical outcome and significant risk factors associated with both morbidity and mortality after EL. Four hundred and twenty-six patients who underwent emergency laparotomy from January 2022 to December 2024 were enrolled. Data were recorded on a structured proforma, and analyzed through SPSS 26.0. Independent predictors of 30-day mortality and major complications were identified using logistic regression. The median age of the study population was 54, 45% were ASA grade III, and 28% were ASA IV– V. The global 30-day mortality rate was 14.6% with major complications (Clavien–Dindo Grade III–V) observed in 25.3% of the patients. Patients included 30.3% needing ICU admission and had a median length of stay of 12 days. Independent predictors of mortality included ASA grade III–V (OR 2.96), age ≥60 years (OR 2.01), preoperative shock (OR 3.42) and diabetes mellitus (OR 1.88). No consultant in supervision during surgery and unavailability of ICU bed correlated significantly with high mortality and complication rates. The patients randomly allocated to checklist guided surgery had less complications and were associated with less mortality (10.1% versus 23.7%, p < 0.001). These observations highlight the contribution of clinical risk factors and perioperative systems on EL among low-resource settings. Given these findings, organization with use of planned surgical safety program, the presence of a consultant from the early stages, and preferential access to ICU can contribute to improved outcomes for this high-risk group of surgical patients.